Evaluating rooftop rainwater harvesting potential to satisfy urban water demand in Hosaena City, South Central Ethiopia - Dawit Yohannes Meskele; Muse Wldmchel Shomre; Tagese Kalsido Soche (Water Supply, 2024)
The assessment of the rainwater harvesting (RWH) potential in Hosaena City from medium to large public buildings is the main objective of the study. ArcGIS with Google Earth Pro was used to calculate the rooftop area of the selected building, and RWH from each category of public buildings was evaluated by considering rooftop areas, monthly rainfall, and runoff coefficient. The result shows that the highest amount of rainwater was harvested from the City Administration building in August (197.1 m3), whereas the lowest was collected from the Health Center building in December (1.8 m3). Additionally, the contribution of RWH from individual public buildings for each month was evaluated, and its values ranged from 0.073 to 1.8%. The comparison shows that Wachemo University, Nigist Eleni Comprehensive Hospital, a technical and vocational institute, and teacher training center buildings, could have a significant potential for rainwater storage, ranging from 1.56 to 28.41%. This implies that, besides saving a noteworthy volume of potable water, the excess rainwater can be stored and utilized for the later dry months. As a result, it is recommended that rooftop RWH in Hosaena be the best source of the city's water supply system to reduce the current water supply shortage. HIGHLIGHTS Rainwater harvesting (RWH) is a suitable technology to store excess rainwater and utilize it for the later dry months.; Medium to large public buildings are the main rooftop area in the field for the RWH system.; Use of RWH technology should reduce the water supply–demand gap in the city.; A large amount of rainwater per month was harvested from City Administration public buildings.;